Thrombus formation and ischemic necrosis of the uterus and adnexa due to purpura fulminans: A case report. Issue 12 (15th September 2021) - Maebayashi, Aki; Hayashi, Nobuki; Kamata, Saki; Sugita, Atsunori; Tang, Xiaoyan; Kawana, Kei
Abstract: Purpura fulminans (PF) is a syndrome characterized by the sudden onset of progressive skin hemorrhage, necrosis of the extremities, and thrombotic occlusion. Although the cause is believed to be protein C deficiency, many aspects of this syndrome have yet to be clarified. A 45‐year‐old Japanese woman, G2P2 (vaginal delivery), developed fever and lower abdominal pain. It was her 5th day of menstruation, and a tampon had been in the vagina for a few days. Septic shock and disseminated intravascular coagulation were diagnosed, and multidisciplinary treatment was started. Also, toxic shock syndrome due to tampon use was suspected. The purpura on the limbs turned into blisters and then blackish‐purple spots, leading to hemorrhagic necrosis within a few days. Moreover, imaging showed that the uterus and both adnexa had enlarged significantly, and raised suspicion of abscess formation. Total hysterectomy and bilateral adnexectomy were performed, and the histopathological diagnosis was hemorrhagic necrosis due to extensive thrombus formation. In men, PF affects the scrotum and penis, leading to autoamputation of the male genitalia, while there are no reports of PF involving the female genitalia. Regarding the PF, in this case, we considered the possibility of pathologic conditions progressing to the female genitalia.